2014
DOI: 10.1063/1.4879779
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-energy differential and integral cross sections for vibrational excitation in α-tetrahydrofurfuryl alcohol

Abstract: Differential and integral cross section measurements, for incident electron energies in the 20-50 eV range, are reported for excitation of several composite vibrational modes in α-tetrahydrofurfuryl alcohol (THFA). Optimisation and frequency calculations, using GAUSSIAN 09 at the B3LYP/aug-cc-pVDZ level, were also undertaken for the two most abundant conformers of THFA, with results being reported for their respective mode classifications and excitation energies. Those calculations assisted us in the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…12). Recently, however, for the biomolecules tetrahydrofuran (THF) 13,14 and tetrahydrofurfuryl alcohol (THFA), 15 it has been demonstrated that the vibrational excitation cross sections persist in magnitude away from the lower-lying shape resonances at a) Author to whom correspondence should be addressed. Electronic mail:…”
Section: Introductionmentioning
confidence: 99%
“…12). Recently, however, for the biomolecules tetrahydrofuran (THF) 13,14 and tetrahydrofurfuryl alcohol (THFA), 15 it has been demonstrated that the vibrational excitation cross sections persist in magnitude away from the lower-lying shape resonances at a) Author to whom correspondence should be addressed. Electronic mail:…”
Section: Introductionmentioning
confidence: 99%
“…In particular we find that at 20 eV, both angular distributions are quasi-isotropic, at 30 eV, there is just a suggestion for their DCS being more forward peaked at the smaller scattered electron angles, while at 40 eV, both angular distributions are now clearly forward peaked in magnitude at smaller θ. The tendency for the angular distributions of composite vibrational modes to be quasi-isotropic, at energies ∼15-20 eV, has been observed by us previously in THF, 5 THFA, 7 pyrimidine, 8 and phenol 11 and still awaits a definitive explanation from theory. The angular distribution results at 40 eV are more understandable in terms of the target molecular properties, in that they exhibit a behaviour consistent with furfural having both a strong permanent dipole moment (3.46-3.57 D 51,52 for the trans conformer), and a dipole polarisability of some magnitude (59.92 a 3 0 53 ).…”
Section: Resultsmentioning
confidence: 97%
“…We believe this is likely to be the case as structurally similar ring-based species such as THF, 3,6,54 THFA, 7 and even pyrimidine 8 all exhibit similar π * shape resonances in that energy regime. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations